Штучний інтелект і право на освіту - Кардаш, А. Є. (ХНУРЕ, 2023)
In contemporary world, technology is developing very rapidly. Artificial intelligence is not exception, it is used in various areas of human life. But because of its functionality, it can be used for both good and bad purposes. One of the most popular applications of artificial intelligence is sphere of education. This article examines the benefits and harms of using AI and how it affects the lives of pupils and students.